2015
DOI: 10.1158/2326-6066.cir-15-0089
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Cancer Vaccine against ALK-Rearranged Lung Tumors

Abstract: Non-small cell lung cancer (NSCLC) harboring chromosomal rearrangements of the anaplastic lymphoma kinase (ALK) gene is treated with ALK tyrosine kinase inhibitors (TKIs), but is successful for only a limited amount of time; most cases relapse due to the development of drug resistance. Here we show that a vaccine against ALK induced a strong and specific immune response that both prophylactically and therapeutically impaired the growth of ALK-positive lung tumors in mouse models. The ALK vaccine was efficaciou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…In fact, these findings are consistent with the notably low immune infiltrating levels in ALK-rearranged NSCLC tumors [50], supportive of the notion that ALK-altered cancers can be immunosuppressive in their microenvironments. In line with these observations, Hong et al successfully demonstrated that anti-PD-1/PD-L1 antibodies could potentially be therapeutic in ALK-rearranged NSCLC [48].…”
Section: Alk Aberrations and Immune Evasion Signalingsupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, these findings are consistent with the notably low immune infiltrating levels in ALK-rearranged NSCLC tumors [50], supportive of the notion that ALK-altered cancers can be immunosuppressive in their microenvironments. In line with these observations, Hong et al successfully demonstrated that anti-PD-1/PD-L1 antibodies could potentially be therapeutic in ALK-rearranged NSCLC [48].…”
Section: Alk Aberrations and Immune Evasion Signalingsupporting
confidence: 81%
“…In ALCL, combination of chemotherapy and ALK DNA vaccine could also prevent in vivo tumor growth and increased survival of lymphoma-bearing mice [61]. This ALK DNA vaccine also resulted in a 60% reduction in tumor number with survival doubling in ALK-positive NSCLC mouse models [50]. Another DNA plasmid-based ALK vaccine was also found to be effective in mounting specific anti-ALK immune response in ALK-positive NSCLC mouse models [62].…”
Section: Alk Neoantigens and Alk Vaccinesmentioning
confidence: 99%
“…The immune targeting of tyrosine kinases is a promising alternative, or complement, to tyrosine kinase inhibitor-based targeted therapies [45,46]. When tyrosine kinases, such as ROS1, are expressed on the plasma membrane, their immune targeting can either be achieved via the passive administration of mAbs or by actively immunizing the patient against the tyrosine kinase.…”
Section: Of 23mentioning
confidence: 99%
“…High PD-L1 expression reduced ALK vaccine efficacy, which could be restored by administration of anti-PD-1 immunotherapy [101]. The hopes and concerns, about combination therapy with ALK-inhibitors and immunotherapy are pretty the same described with EGFR mutations, with a special interest in adverse events Ongoing but not recruiting [98] 10.…”
Section: Future Perspectives In Alk-rearranged Nsclcmentioning
confidence: 99%